Validación estructural del R-SPQ-2F: Un análisis factorial confirmado - Merino Soto, Cesar (2014)
The aim of this study is to validate the internal structure of the Revised-Study Process Questionnaire-2 Factors (Biggs, Kember & Leung, 2001), through a heterogeneous sample of 269 university and non-university participants. The structural equation methodology is used to test several measurement models: one-dimensional, four factors and hierarchical structure, and two factors (orthogonal and oblique).Theodels based on four factors did not show a satisfactory adjustment, and one had convergence problems caused by a very high interfactorial correlation. The two-factor model (deep and shallow) with correlated errors had a satisfactory adjustment. The internal consistency was satisfactory. The usefulness of the instrument and its theoretical reformulation is discussed.